Efektivitas Layanan Konseling Kelompok Untuk Mengurangi Kecemasan Akademik Siswa SMP Negeri 2 Praya - Silvia Arum Jayanti; Monica Rahayu (Educational Note, 2026)
This study aims to determine the effectiveness of group counseling services in reducing students’ academic anxiety at SMP Negeri 2 Praya. Academic anxiety is one of the psychological problems frequently experienced by students, especially when facing examinations or other academic pressures, which negatively affect motivation, concentration, and academic achievement. This research employed a quantitative approach using a pretest–posttest experimental group design. The research subjects were 10 eighth-grade students selected through purposive sampling based on the identification of high levels of academic anxiety. The instrument used was an academic anxiety scale that had been tested for validity and reliability. Group counseling services were conducted in six sessions using a humanistic approach, focusing on increasing self-awareness, emotional regulation, and adaptive coping strategies. Data analysis using the Wilcoxon test indicated a significant decrease in academic anxiety levels after participating in group counseling services (p < 0.05). These findings suggest that group counseling is effective in helping students overcome academic anxiety. This study recommends that school guidance and counseling teachers actively implement group counseling services as both preventive and curative efforts to address students’ psychological problems, particularly academic anxiety. The implications of these results are important for the development of guidance and counseling programs that are responsive to students’ emotional and academic needs at the junior high school level.